Epitranscriptomic rRNA fingerprinting reveals tissue-of-origin and tumor-specific signatures - Milenkovic, Ivan; Cruciani, Sonia; Llovera, Laia; Lucas, Morghan C.; Medina, Rebeca; Pauli, Cornelius; Heid, Daniel; Muley, Thomas; Schneider, Marc; Klotz, Laura Valentina; Allgäuer, Michael; Lattuca, Ruben; et al. (Molecular cell, 2025)
Mammalian ribosomal RNA (rRNA) molecules are highly abundant RNAs, decorated with over 220 rRNA modifications. Previous works have shown that some rRNA modification types can be dynamically regulated; however, how and when the mammalian rRNA modification landscape is remodeled remains largely unexplored. Here, we employ direct RNA sequencing to chart the human and mouse rRNA epitranscriptome across tissues, developmental stages, cell types, and disease. Our analyses reveal multiple rRNA sites that are differentially modified in a tissue- and/or developmental stage-specific manner, including previously unannotated modified sites. We demonstrate that rRNA modification patterns can be used for tissue and cell-type identification, which we hereby term “epitranscriptomic fingerprinting.” We then explore rRNA modification patterns in normal-tumor matched samples from lung cancer patients, finding that epitranscriptomic fingerprinting accurately classifies clinical samples into normal and tumor groups from only 250 reads per sample, demonstrating the potential of rRNA modifications as diagnostic biomarkers.
Onlline veröffentlicht: 10. Dezember 2024
Gesehen am 19.08.2025